(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The essence of innovation, innovation and innovation process. Posted to determine their proposed concepts based on critical reflection of previous definitions. Highlight delimitation criteria of innovation, innovation process and innovative development of enterprise in the new economy. The analysis criteria enabling these concepts we offer both understand the process of innovation introducing new innovative solutions in the manufacturing sector of the company for the development of new technologies, improving production and updating of products, welfare workers, improving key performance indicators and increasing investment attractiveness. The innovation process involves a change in the manufacturing, process technology, development and implementation of progressive ideas in practical activities of enterprises and their commercialization. Innovation means creating enterprise development, implementation and commercialization of innovations that will ensure qualitative changes of control object, social, economic, environmental effects, sustained growth of profitability, investment attractiveness in the long term. Thus, innovation and the innovation process is the object of the enterprise system innovation. Innovation – the process of introducing new innovative solutions in all areas of the company for the development of new technologies, improving production and updating products as a result of improved key performance indicators and increasing the investment attractiveness of the company. Innovative development – the creation, implementation and commercialization of innovations that will ensure qualitative changes, social, economic, environmental effects and steady growth of profitability of investment attractiveness in the long term. Under the innovative process mean change in production, process technology, the development and implementation of progressive ideas in practical activities of enterprises and their commercialization. Innovation is defined as the introduction of our new innovative solutions in all areas of the company for the development of new technologies, improving production and updating of products, welfare workers, improving key performance indicators and increasing investment attractiveness. Found that innovation is the foundation of the innovation process. On the basis of the concepts of «innovation», «innovation process», «innovative development» we have identified a common point – innovation used in the innovation process and provides innovative development company. It is the basis of these processes without the participation of other concepts have no economic content. Criteria definitions and their separation promote the formation of approaches to evaluation of innovative methodological foundations of enterprises.